1
$\begingroup$

Suppose I have the state space system $a\dot{x} = -x + \frac{1}{k}h(x) + u$, and output $y = h(x)$, where $a,k > 0$. The only information I'm given about $h(x)$ is that $h\in[0,k]$. I want to show that the system is passive using the storage function $V(x) = a\int_{0}^{x}h(\sigma)\ d\sigma$. The definition of a passive system is $u^\intercal y \geq \dot{V}$ for all $(x,u)$. Thus,

$$ \dot{V} = ah(x) \dot{x} = h(x) (-x + h(x)/k + u) = \frac{1}{k}h(x)(h(x) - kx) + h(x) u. $$

Rearranging this gives

$$ h(x)u = yu = \dot{V} + \frac{1}{k}h(x)[kx-h(x)]. $$

In order to prove passivity, I need to show that $\frac{1}{k}h(x)[kx - h(x)] \geq 0$, for all $x$. However, all I'm given is that $h\in[0,k]$ so how can this be true in general? Am I missing something really simple here?

$\endgroup$
0
$\begingroup$

In your problem, you define the supply rate (I will name it $s$) $s(y,u)=u^{\top}y$. And it is (strict) passive if $\dot{V} \leq s(y,u)$. I also consider that you are working taking the case where this consideration is valid $u^{\top}y \equiv uy$.

Saying that, I believe you can re-arrange your equation as follows: \begin{align*} \dot{V}(x) &= uy+\frac{1}{k}y^2-xy \\ &=y(u+\frac{1}{k}y) -xy \end{align*} then define as the new input $\nu := u+\frac{1}{k}y$, in that sense you will have the following equation: \begin{align*} \dot{V}(x) &= y\nu-xy\leq \nu y \end{align*}

The system is (strict) passive if $xh(x)> 0\quad\forall x\in\mathbb{R}$.

| improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.